INNOVATIVE AND RESEARCH AND PRODUCTION POTENTIAL OF THE AGRARIAN SECTOR: FINANCING - Babadjanov Abdirashid Musayevich (Ecominds Press, 2025)
This article reveals the main content of innovative and scientific and production potential of the agrarian sector, sets out approaches to its structure, theoretical, methods and methodological foundations of innovation are studied, scientific potential corresponding to the strategy of innovative development of the country's economy is emphasized, production potential and financial issues of agriculture are considered. The relationship between the financing of each type of agriculture and the total amount of funds spent is considered. In addition, the farm and peasant farm require an efficient source of financing. The study of the innovative potential of agrarian production will allow analyzing the efficiency of resource use in order to achieve sustainable and effective socio-economic growth in the country's agrarian sector, develop and substantiate recommendations when making decisions under the conditions of limited resources. The fact is that government spending on agricultural finance is likely to be at a very high level, which is accompanied by a significant positive correlation of industry performance.
Keywords: Agrarian sector, innovation potential, scientific potential, production potential, intellectual, agricultural financing, development, economy, improvement.